Hãy luôn nhớ cảm ơn và vote 5*
nếu câu trả lời hữu ích nhé!
2774
1715
`a)`
`A=(2+sqrtx)(1/[sqrtx+2]-1/[2-sqrtx]-x/[x-4]) (x>=0; x ne 4)`
`A=(2+sqrtx)[1/[sqrtx+2]+1/[sqrtx-2]-x/[(sqrtx-2)(sqrtx+2)]]`
`A=(2+sqrtx)*[sqrtx-2+sqrtx+2-x]/[(sqrtx-2)(sqrtx+2)]`
`A=(2+sqrtx)*[2sqrtx-x]/[(sqrtx-2)(sqrtx+2)]`
`A=(2+sqrtx)*[-sqrtx(sqrtx-2)]/[(sqrtx-2)(sqrtx+2)]`
`A=-sqrtx`
`b)`
Tại `x=1.44(text[n])` ta có
`A=-sqrt[1.44]`
`A=-1.2`
`c)`
`A=-8` khi
`-sqrtx=-8`
`-> sqrtx=8`
`-> x=64(text[n])`
Vậy `x=64`
Hãy giúp mọi người biết câu trả lời này thế nào?
`a)` `A = (2 + sqrtx)(1/(sqrtx+2) - 1/(2 - sqrtx) - x/(x-4)) (x >= 0; x ne 4)`
`= (sqrtx + 2)[1/(sqrtx+2) + 1/(sqrtx-2) - x/((sqrtx-2)(sqrtx+2))]`
`= (sqrtx+2) * ((sqrtx-2) + (sqrtx+2) - x)/((sqrtx-2)(sqrtx+2))`
`= (sqrtx - 2 + sqrtx + 2 - x)/(sqrtx-2)`
`= (2 sqrtx - x)/(sqrtx-2)`
`= -sqrtx`
`b)` Thay `x = 1,44 (tm)` vào `A`, ta được:
`A = -sqrt(1,44) = -1,2`
Vậy `A = 1,2` khi `x = 1,44`
`c)` `A = -8` khi:
`-sqrtx = - 8 to sqrtx = 8 to x =64 (tm)`
Vậy `x = 64` thỏa mãn `A = -8`.
Hãy giúp mọi người biết câu trả lời này thế nào?
Bảng tin